Handbook of herbs and spices. - Peter, K. V. (Woodhead Publishing in food science and technology., 2004)
Together with its companion volumes, Handbook of herbs and spices: Volume 2 provides a comprehensive and authoritative coverage of key herbs and spices. Chapters on individual plants cover such issues as description and classification, production, chemical structure and properties, potential health benefits, uses in food processing and quality issues.